Research on The Development of Youth Character Education: Take Chinese Perspective - Lingmin Zhang (Ilmu Inovasi Nusantara, 2023)
In order to understand the status quo of adolescent character education and to promote the formation of excellent quality, this paper uses literature research and qualitative analysis to study adolescent character education. Firstly, this paper's research literature on adolescent education through retrieval analyzes the existing theoretical achievements from four dimensions of connotation, problems, strategies, and enlightenment of character education for teenagers and understanding its prior status and progress. And then the findings are as follows: the research results of youth character education in the world could be better. Astonishingly, in recent years, Chinese scholars' research on youth character education is still rare. The findings indicate that more than the emphasis on adolescent personality education is needed. Based on theoretical literature, take the Chinese perspective and set two suggestions: follow the regular and pay attention to practice. Firmly believe these theoretical results should be combined with practice to achieve educational goals. This paper has theoretical and practical significance in developing excellent youth character and the perfection of the theoretical system of adolescent character education